Surgical Management Of Dentigerous Cyst In A Buffalo - Parihar, A.S.; Shukla , B.P.; Verma , S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The dentigerous cysts are congenital anomalies which appears at early stages of organogenesis. The cystic structure is generally developed together with hetero-topic polydontia (Wapf and Nuss, 2005; Brown et al., 2007). The cystic changes frequently originate from the sites of teeth localisations. They are occasionally found on maxilla, mandible or muscle tissue and are associated with the gingiva. The cystic odontoma on ventral aspect of mandible was reported in buffalo (Purohit et al., 2012). On the other hand, malformed unerupted teeth and their remnants develop from the mesenchymal parts of tissues of dental papilla, cementum and periodontium or oral mucosa (Rüsse,1998; Wapf and Nuss,2005).